Effects of urea ammonia pretreatment on the batch anaerobic fermentation efficiency of corn stovers - Li, Qiang; Yang, Fuli; Zheng, Guoxiang; Guan, Zhengjun (International Journal of Agricultural and Biological Engineering, 2019)
In order to enhance the biogas production and provide nitrogen sources for the growth of microorganisms, experiments on urea ammonia pretreatment of corn stovers were implemented at (35±1)°C to investigate the effects of urea ammonia pretreatment on the batch anaerobic fermentation efficiency of corn stovers. This study assessed the effects of urea ammonia contents (2%, 4%, and 6%) and moisture contents (30%, 50%, 70% and 90%) on the physical structures of lignocelluloses and the efficiency of biogas production from anaerobic fermentation of corn stovers. The results indicated that the methane production reached 230.31 mL/g VS (volatile solids) at pretreatment with 4% urea ammonia and 70% moisture contents for the batch anaerobic fermentation, which was 26.6% higher than that of the untreated group. The degradation rates of cellulose and hemicellulose were 66.34% and 75.47% after the anaerobic fermentation, respectively, which were about 22.6% and 20.9% higher than that of the untreated group, respectively. Thus, it was concluded that urea ammonia pretreatment can improve the efficiency of biogas production from anaerobic fermentation of corn stovers.Keywords: corn stovers, urea ammonia pretreatment, batch anaerobic fermentation, methane production, degradationDOI: 10.25165/j.ijabe.20191204.4835Citation: Li Q, Yang F L, Zheng G X, Guan Z J. Effects of urea ammonia pretreatment on the batch anaerobic fermentation efficiency of corn stovers. Int J Agric & Biol Eng, 2019; 12(4): 169–173.